Computational Validation of the Best Tuning Method for a Vehicle-Integrated PID Controller. (25th June 2022) - Manuel, Calequela J. T.; Santos, Max M. D.; Lenzi, Giane G.; Tusset, Angelo M.
Abstract : This paper validates and analyzes the robustness of the proportional-integral-derivative (PID) action controller from an open transfer function that integrates a proportional-integral (PI) action controller to obtain the response of a robust action control during the automatic parking maneuver of a vehicle where the simulations are based on 3 adjustment methods: Ziegler-Nichols (ZN), Chien-Hrones-Reswick (CHR), and Cohen-Coon (CC), and as a result of the computer simulations, it is determined the best performance index of the PID controller represented by mathematical and graphic equations with the help of MATLAB/Simulink software.